If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1)(x + -5)(x + -8) = 0 Reorder the terms: (-1 + 2x)(x + -5)(x + -8) = 0 Reorder the terms: (-1 + 2x)(-5 + x)(x + -8) = 0 Reorder the terms: (-1 + 2x)(-5 + x)(-8 + x) = 0 Multiply (-1 + 2x) * (-5 + x) (-1(-5 + x) + 2x * (-5 + x))(-8 + x) = 0 ((-5 * -1 + x * -1) + 2x * (-5 + x))(-8 + x) = 0 ((5 + -1x) + 2x * (-5 + x))(-8 + x) = 0 (5 + -1x + (-5 * 2x + x * 2x))(-8 + x) = 0 (5 + -1x + (-10x + 2x2))(-8 + x) = 0 Combine like terms: -1x + -10x = -11x (5 + -11x + 2x2)(-8 + x) = 0 Multiply (5 + -11x + 2x2) * (-8 + x) (5(-8 + x) + -11x * (-8 + x) + 2x2 * (-8 + x)) = 0 ((-8 * 5 + x * 5) + -11x * (-8 + x) + 2x2 * (-8 + x)) = 0 ((-40 + 5x) + -11x * (-8 + x) + 2x2 * (-8 + x)) = 0 (-40 + 5x + (-8 * -11x + x * -11x) + 2x2 * (-8 + x)) = 0 (-40 + 5x + (88x + -11x2) + 2x2 * (-8 + x)) = 0 (-40 + 5x + 88x + -11x2 + (-8 * 2x2 + x * 2x2)) = 0 (-40 + 5x + 88x + -11x2 + (-16x2 + 2x3)) = 0 Combine like terms: 5x + 88x = 93x (-40 + 93x + -11x2 + -16x2 + 2x3) = 0 Combine like terms: -11x2 + -16x2 = -27x2 (-40 + 93x + -27x2 + 2x3) = 0 Solving -40 + 93x + -27x2 + 2x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 2ab+a+5ab+b= | | x^2+35x+19= | | 9-x=1+x+18 | | x=2x-4 | | 78-4x=14x+20 | | 9-9x=41-23x | | 3x+6=62-4x | | 5x+23=13x-73 | | 7x-28=49 | | 4(x-2)=x+5(x-4) | | 3x^2-2x-133=0 | | -2-3x=3-x | | 5(x-15)=-2(18-x) | | -3x-x=3+5x | | y=5x^2-6x-95 | | 2x-yx+4y=12 | | x^2+13x+32=0 | | 9x+10y=74 | | 4-3(4a+5)=5(7-4a) | | 7x+3=3x-21 | | 11(t-3)+3t=7(3t+5)-11 | | -5x^2-25x-30=0 | | -0.0833333x=-1-0.1666666y | | -0.0833333x=-1-0.1666666 | | 17-16x=3-2x | | 0=-2y+4-7x | | -3+3x=-2(x+1) | | .5y-6=.1428571429y | | 6x+7=8x-15 | | 3x^3-36x^2+108x=0 | | 4a-2b+3=4 | | 4+3(x+2)=10 |